Social conditionality of criminal responsibility for torture - Телесніцький, Геннадій Никонович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
Article is devoted to the social conditionality of criminal liability for torture. The factors that determinesuch conditionality are set: international-legal, national-legal, criminological, social and psychological. The conclusions are made and proposals for improvement of the relevant criminal-legal provisions are formulated.